Identification and expression of genes narL and narX of the nar (nitrate reductase) locus in Escherichia coli K-12. - Stewart, V (1988)
Previous studies have shown that narL+ is required for nitrate induction of nitrate reductase synthesis and for nitrate inhibition of fumarate reductase synthesis in Escherichia coli. We cloned narL on a 5.1-kilobase HindIII fragment. Our clone also contained a previously unidentified gene, which we propose to designate as narX, as well as a portion of narK. Maxicell experiments indicated that narL and narX encode proteins with approximate MrS of 28,000 and 66,000, respectively. narX insertion mutations reduced nitrate reductase structural gene expression by less than twofold. Expression of phi (narL-lacZ) operon fusions was weakly induced by nitrate but was indifferent to aerobiosis and independent of fnr. Expression of phi (narX-lacZ) operon fusions was induced by nitrate and was decreased by narL and fnr mutations. A phi (narK-lacZ) operon fusion was induced by nitrate, and its expression was fully dependent on narL+ and fnr+. Analysis of these operon fusions indicated that narL and narX are transcribed counterclockwise with respect to the E. coli genetic map and that narK is transcribed clockwise.